(untitled) (Research, Society and Development, 2022)
With the worsening of the new coronavirus pandemic (SARS-CoV-2), Brazil and the whole world came to a standstill, especially in interpersonal relationships, because the infectious agent ended up interrupting physical contact and the routine of countless people in a drastic way, especially for the public of basic education in the process of cognitive formation. Given this scenario, the study presented had the objective of analyzing the implications of social isolation for students in the initial stages of education, the problem of classes in a virtual environment for the teaching-learning process, and the impacts and perspectives for the future of Brazilian students. The methodology used consists of a bibliographic review, of a qualitative nature, with its elaboration done by reading books, scientific articles and official sites for a better structuring of the intended premises. Through the analyses, it was possible to verify that in this atypical conjuncture, teachers were overloaded, because they had to adapt to the use of educational technologies in a short period of time and needed to renew the way of transmitting knowledge. As for the students, many faced obstacles to follow the remote classes, due to the lack of necessary equipment and internet connection problems, which caused an increase in school dropouts. Thus, through this research, it was possible to conclude that education suffered a setback in this pandemic period, which culminated in numerous difficulties faced by educators and students, both in school and in private life, which highlights the complex task of Brazilian public education for the coming years.